Obstructed hemivagina and ipsilateral renal anomaly (OHVIRA) syndrome: A case report - Mohamed Amin Elgohary; Rushikesh Naik; Mohamed Elkafafi; Hussein Hamed; Yaser Ali (Elsevier, 2023)
Background: Obstructed hemivagina and ipsilateral renal anomaly (OHVIRA) or Herlyn-Werner-Wunderlich syndrome, is a rare Mullerian duct anomaly with uterus didelphys, unilateral obstructed hemivagina, and ipsilateral renal agenesis. Patients with this anomaly usually present after menarche with pelvic pain and/or an abdominal mass. Case presentation: We are reporting a case of an 11-year-old girl with lower abdominal pain and lower abdominal tenderness in whom radiological investigations confirmed the diagnosis of OHVIRA syndrome. The case was managed successfully by excision of the vaginal septum. Conclusion: The triad of uterine didelphys, obstructed hemivagina, and ipsilateral renal anomaly, known as OHVIRA syndrome, is a rare congenital anomaly. It represents a diagnostic dilemma because of the regular menstruation and nonspecific lower abdominal pain. Health care providers should be aware of the presentation and diagnosis of this condition to facilitate early and accurate management.